Nursing Personnel Needs Analysis Using the Workload Indicator Staff Need (WISN) Method in Installation Emergency Datu Beru Hospital Central Aceh - Deby Yulliswandi; Megawati Megawati; Nuraini Nuraini (Newinera Publisher, 2022)
WISN is a resource management tool that analyzes staffing needs based on the workload for a certain staff category, as well as the facility and kind of health institution. This tool can be applied nationally, regionally, and to health facilities. It is simple to use on a technical, comprehensive, and practical level, and it facilitates the determination of variations in human resource requirements among various types of health services, such as health centers and hospitals. This study's objective is to examine the requirement for workload-based nursing staff utilizing the Workload Indicator Staff Need (WISN) approach at the Emergency Installation (IGD) Datu Beru Hospital, Central Aceh in 2021. A descriptive study using observational methods served as the research design. This study's population consisted of all 35 nurses at the Emergency Installation of RSUD Beru Takngon. This population was sampled using a total sample size of 35. 35 individuals. WISN analysis was used to analyze the data. After the researcher got data from completing the questionnaire based on observation, they recorded and made revisions to the documentation of the nurses' work in the emergency room. Research findings Using the WISN approach, it is determined that the Datu Beru Takengon Hospital Emergency Room has a nursing staff shortfall of three individuals. Working time, nursing staff activities, workload standards, the slack factor, and the nursing staff needs calculation have an effect on the nursing staff needs at the Emergency Installation of RSUD Datu Beru Takengon.